Feasible integration in asphalt of piezoelectric cymbals for vibration energy harvesting. (15th March 2016) - Moure, A.; Izquierdo Rodríguez, M.A.; Rueda, S. Hernández; Gonzalo, A.; Rubio-Marcos, F.; Cuadros, D. Urquiza; Pérez-Lepe, A.; Fernández, J.F.
Graphical abstract: A system based on piezoelectric cymbals embedded in asphalt for the first time is used as harvester for wasted vibrational energy produced by traffic. Energy density in the range of other alternative sources is achieved, with an estimated projected cost that shows the feasibility of this harvesting energy system. Highlights: Piezoelectric cymbals have been directly integrated in asphalt for the first time. Harvesting from wasted vibrational energy caused by vehicles is demonstrated to be feasible by this integration. Energy density and cost are estimated to be competitive with other sources as photovoltaic. A 10% of the energy generated in the Region of Madrid can be obtained by covering only the 0.6% of its roads. Abstract: Piezoelectric cymbals with 29-mm diameter and different configurations are fabricated and tested to determine the best conditions to optimize the conversion of mechanical to electric energy. Then, the ones with the best results are integrated directly in asphalt to evaluate their performance as vibration energy harvesters in roads, in a test bench designed to characterize these parameters. The main cymbal parameters and their integration in the asphalt are determined. For the first time, the electrical energy that can be obtained with the embedment of cymbals in asphalt is evaluated. Each single piezoceramic cymbal recovers up to 16 μW for the pass of one heavy vehicle wheel. An extrapolation of the energy transformed by the integrated cymbals in roads with high vehicle densities, such as in a peri-urban motorway, is approached. Energy densities in the range of 40–50 MW h/m 2 can be obtained at 100 m of road (use of 30, 000 cymbals), which could account for more than 65 MW h in a year. All this with a relatively low cost for an emerging technology (less than 2 €/kW h). The conversion of wasted and unused vibrational energy in roads by piezoelectric cymbals is thus proved as a real possibility of energy harvesting.